2019
DOI: 10.1515/jiip-2018-0023
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of a crack with the incident waves and measurements inside a penetrable cavity

Abstract: The inverse scattering problem of determining a crack outside a known penetrable cavity from the measurements and point sources placed in a closed curve Λ inside the cavity is considered. The factorization method is used to reconstruct the crack on which the mixed-type boundary conditions are posed. To this end, we need to overcome two key difficulties. One of them is to find the relationship between the two data-to-data operators, which map the boundary data on the crack to the values of scattered fields on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Recently, Zhang et al [33] proposed the idea of using a reference ball and the superimposition of two point sources as incident waves, and proved that the position, shape and boundary conditions of the cavity can be uniquely determined from phaseless near-field data. More studies on the inverse scattering problems of the cavities can also be found in [2,10,25].…”
mentioning
confidence: 99%
“…Recently, Zhang et al [33] proposed the idea of using a reference ball and the superimposition of two point sources as incident waves, and proved that the position, shape and boundary conditions of the cavity can be uniquely determined from phaseless near-field data. More studies on the inverse scattering problems of the cavities can also be found in [2,10,25].…”
mentioning
confidence: 99%